2013
DOI: 10.1128/iai.01265-12
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Psoriasin (S100A7) and Koebnerisin (S100A15) in the Brain

Abstract: The expression and function of psoriasin in the brain have been insufficiently characterized. Here, we show the induction of psoriasin expression in the central nervous system (CNS) after bacterial and viral stimulation. We used a pneumococcal meningitis in vivo model that revealed S100A15 expression in astrocytes and meningeal cells. These results were confirmed by a cell-based in vivo assay using primary rat glial and meningeal cell cultures. We investigated psoriasin expression in glial and meningeal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
(62 reference statements)
2
15
0
Order By: Relevance
“…Human β -defensin 2 (hBD2), which is encoded by DEFB4 , has been previously described to diminish Mtb growth in a resazurin assay [ 17 ] and was a potent inhibitor of growth of Mtb H37Rv ( Fig 8A ) and clinical strains in our hands ( S5A Fig ). Because, no bioactive form of S100A7A was available, we used the close homologue S100A7 [ 23 ], known as psoriasin, which was also induced in an IL1β-dependent manner in co-culture ( S5B and S5C Fig ) and reflected the induction pattern observed for S100A7A ( Fig 3 ). Psoriasin decreased the median Mtb burden in liquid culture significantly by 62% ( Fig 8B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human β -defensin 2 (hBD2), which is encoded by DEFB4 , has been previously described to diminish Mtb growth in a resazurin assay [ 17 ] and was a potent inhibitor of growth of Mtb H37Rv ( Fig 8A ) and clinical strains in our hands ( S5A Fig ). Because, no bioactive form of S100A7A was available, we used the close homologue S100A7 [ 23 ], known as psoriasin, which was also induced in an IL1β-dependent manner in co-culture ( S5B and S5C Fig ) and reflected the induction pattern observed for S100A7A ( Fig 3 ). Psoriasin decreased the median Mtb burden in liquid culture significantly by 62% ( Fig 8B ).…”
Section: Resultsmentioning
confidence: 99%
“…Antimycobacterial effects of selected peptides were performed in 96 well plates. hBD2 (PeproTech, London, UK), S100A7/Psoriasin (a kind gift from Prof. Joachim Grötzinger [ 23 ]) and controls were diluted in fresh 7H9 and Mtb bacilli harvested in mid-log phase was added. Plates were incubated shaking for up to 7 days at 36°C.…”
Section: Methodsmentioning
confidence: 99%
“…Mice lacking CRAMP were more susceptible to meningococcal infection and exhibited increased bacterial growth in the blood, liver, and spleen [29]. In a previous work, we emphasized the importance of AP in CNS infections by revealing increased synthesis of the human cathelicidin LL-37 and S100 protein psoriasin in the cerebrospinal fluid of patients suffering from bacterial meningitis [12,13]. In addition, our in vitro studies revealed an increase in rat CRAMP in glial and meningeal cells after exposure to bacterial components [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Our own previous investigations revealed increased levels of the AP cathelicidin LL-37 and psoriasin in the cerebrospinal fluid of patients suffering from bacterial meningitis [12,13]. In humans, one gene is known for cathelicidin.…”
Section: Introductionmentioning
confidence: 99%
“…The cathelicidin of mice and rats is called cathelin-related antimicrobial peptide (CRAMP) [ 8 ] and rCRAMP [ 9 ], respectively. Own investigations revealed an increase of LL-37 and psoriasin (another AMP) in the cerebrospinal fluid (CSF) of patients suffering from bacterial meningitis [ 10 , 11 ]. Bacterial infection and exposure of glial cells to bacterial supernatants and bacterial virulence factors induced an increase of rCRAMP and increased the release of pro- as well as anti-inflammatory cytokines [ 10 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%